Law No. 62 Of The Year 2016 On Cancelling Decree-law No. 35 Of The Year 2014 on the Summer Time System = قانون رقم 62 لسنة 2016 بشأن إلغاء القرار بقانون رقم 35 لسنة 2014 بشأن التوقيت الصيفى - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic